2020
DOI: 10.1097/icl.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinase 9 in Ocular Surface Disorders

Abstract: Objectives: (1) To explore the role and significance of Matrix Metalloproteinase 9 (MMP-9), a proteolytic enzyme, in various ocular surface diseases of inflammatory, infectious, and traumatic etiology (2), to further elucidate the molecular mechanisms responsible for its overexpression in ocular surface disease states, and (3) to discuss possible targets of therapeutic intervention. Methods: A literature review was conducted of primary sources from 1995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…Published reports on infections following LASIK found that severe visual acuity reductions were significantly more associated with keratomycosis rather than bacterial and mycobacterial infections [ 14 ]. Biomechanically weakening, lack of commercially available antifungal eye drops, usage of steroids [ 15 ], and delayed diagnosis might be held responsible for the aggressive course of fungal keratitis after LASIK. It is noteworthy to mention that the high rate of treatment failure in eyes with Aspergillus species may be attributed to the perpendicular growth pattern of fungal filaments that made the infection penetrate quickly deep into the corneal layers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Published reports on infections following LASIK found that severe visual acuity reductions were significantly more associated with keratomycosis rather than bacterial and mycobacterial infections [ 14 ]. Biomechanically weakening, lack of commercially available antifungal eye drops, usage of steroids [ 15 ], and delayed diagnosis might be held responsible for the aggressive course of fungal keratitis after LASIK. It is noteworthy to mention that the high rate of treatment failure in eyes with Aspergillus species may be attributed to the perpendicular growth pattern of fungal filaments that made the infection penetrate quickly deep into the corneal layers [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…61,62 MMP-9 over expression has been shown in dry eye. 63 Kelch-like ECH-associated protein 1 (Keap1)-Nrf2-antioxidant response element pathway has a pivotal role in the regulation of expression of antioxidants genes, maintaining antioxidant status in the corneal epithelial cells and thus protecting ocular surface from the dry eye disease. 64,65 Therefore, activation of Nfr-2 in the corneal epithelial cells can indirectly increase the antioxidant defense such as SOD, CAT and GPx.…”
Section: Dry Eye Diseasementioning
confidence: 99%
“…Pediatric patients have a greater risk of postoperative inflammatory [9]. Postoperative steroid should be used cautiously in patients with brittle cornea syndrome due to the negative effects of steroids on collagen synthesis as well as the risk of secondary glaucoma development [10]. The management of comorbidities also becomes complicated by the graft.…”
Section: Case Reports In Ophthalmological Medicinementioning
confidence: 99%
“…Glaucoma is the leading cause of irreversible blindness postkeratoplasty [15] and is a leading cause of graft failure [10]. Glaucoma management in pediatric patients is challenging due to the lack of cooperation of these patients.…”
Section: Case Reports In Ophthalmological Medicinementioning
confidence: 99%